A model to predict cardiovascular events in patients with newly diagnosed Wegener's granulomatosis and microscopic polyangiitis. - Suppiah, R; Judge, A; Batra, R; Flossmann, O; Harper, L; Höglund, P; Javaid, M; Jayne, D; Mukhtyar, C; Westman, K; Davis, J; Hoffman, G; et al. (2011)
OBJECTIVE: To create a prognostic tool to quantify the 5-year cardiovascular (CV) risk in patients with newly diagnosed Wegener's granulomatosis (WG) and microscopic polyangiitis (MPA) without premorbid CV disease. METHODS: We reviewed CV outcomes during the long-term followup of patients in the first 4 European Vasculitis Study Group (EUVAS) trials of WG and MPA. CV events were defined as CV death, stroke, myocardial infarction, coronary artery bypass graft, or percutaneous coronary intervention. Logistic regression was performed to create a model to predict the absolute risk of a CV event. The model was tested using the Wegener's Granulomatosis Etanercept Trial (WGET) cohort. RESULTS: Seventy-four (13.8%) of 535 patients with 5 years of followup from the EUVAS trials had at least 1 CV event: 33 (11.7%) of 281 WG versus 41 (16.1%) of 254 MPA. The independent determinants of CV outcomes were older age (odds ratio [OR] 1.45, 95% confidence interval [95% CI] 1.11-1.90), diastolic hypertension (OR 1.97, 95% CI 0.98-3.95), and positive proteinase 3 (PR3) antineutrophil cytoplasmic antibody (ANCA) status (OR 0.39, 95% CI 0.20-0.74). The model was validated using the WGET cohort (area under the receiver operating characteristic curve of 0.80). CONCLUSION: Within 5 years of diagnosis of WG or MPA, 14% of patients will have a CV event. We have constructed and validated a tool to quantify the risk of a CV event based on age, diastolic hypertension, and PR3 ANCA status in patients without prior CV disease. In patients with vasculitis, PR3 ANCA is associated with a reduced CV risk compared to myeloperoxidase ANCA or negative ANCA status.